Facile S(N)2 ' coupling reactions of wittig reagents with dimethyl bromomethylfumarate: synthesis of enes, dienes, and related natural products - Patel, Ramesh M.; N. P. Argade (Journal of Organic Chemistry, 2007)

Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide

Bromine-induced facile synthesis of butenolides and spirobutenolides from sterically congested tetrasubstituted dialkyl alkylidene succinates - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2010)
Starting from sterically congested tetrasubstituted dialkyl alkylidene succinates, facile general approach to several dialkyl substituted butenolides and spirobutenolides with the generation of quaternary carbon center has been demonstrated via bromine-induced dealkylative regioselective intramolecular cyclization and dehydrobromination pathway. The mechanistic aspects involved in the formation of butenolides have been also described in brief.
Keywords: alkylidene succinates; bromine; butenolides; intramolecular cyclizations; spirobutenolides

General approach to 2,4-dialkyl-3-carboxybutyrolactones: an efficient synthesis of (+/-)-striatisporolide A and (+/-)-lichesterinic acid - Patel, Ramesh M.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
Starting from 2-alkylidene-3-methylsuccinimides, simple and efficient synthesis of the natural products striatisporolide A. lichesterinic acid and lichesterylic acid have been demonstrated via an acid catalyzed hydrolysis, esterification, OsO(4)-dihydroxylation and dehydrative cyclization pathway.
Keywords: 2-Alkylidene-3-methylsuccinimides; dehydrative cyclizations; lichesterinic acid; OsO(4)-dihydroxylation; striatisporolide A; synthesis

Chemoenzymatic total synthesis of potent HIV RNase H inhibitor (-)-1,3,4,5-tetragalloylapiitol - Batwal, Ramesh U.; Patel, Ramesh M.; N. P. Argade (Tetrahedron-Asymmetry, 2011)
Starting from racemic dimethyl 2-acetoxy-3-methylenesuccinate, the chemoenzymatic facile total synthesis of (-)-1,3,4,5-tetragalloylapiitol has been demonstrated via an efficient lipase catalyzed resolution followed by a DIBAL reduction-double gallyolation, osmium tetroxide dihydroxylation-double gallyolation, and reductive global O-benzyl deprotection pathway. (C) 2010 Elsevier Ltd. All rights reserved.

Regio- and stereoselective selenium dioxide allylic oxidation of (E)-dialkyl alkylidenesuccinates to (Z)-allylic alcohols: synthesis of natural and unnatural butenolides - Patel, Ramesh M.; Puranik, Vedavati G.; N. P. Argade (Organic & Biomolecular Chemistry, 2011)
The first SeO(2) induced (Z)-selective allylic alcohol formation of dialkyl alkylidenesuccinates has been demonstrated to accomplish one-step syntheses of several essential butenolides and fused butenolides via an unusual E- to Z- carbon-carbon double bond isomerisation followed by the lactonization pathway. The observed regio- and stereoselective SeO(2) allylic oxidation protocol has also been extended to the diastereoselective total synthesis of bioactive natural product isomintlactone, its direct conversion to mintlactone and an example of the base-catalyzed intramolecular rearrangement of gamma-lactone to delta-lactone.

Palladium-promoted [2+2+2] cocyclization of arynes and unsymmetrical conjugated dienes: synthesis of justicidin B and retrojusticidin B - Patel, Ramesh M.; N. P. Argade (Organic Letters, 2013)
A facile synthesis of natural and unnatural arylnaphthalenes has been demonstrated via the unprecedented palladium-promoted [2 + 2 + 2] cocyclization of arynes and unsymmetrical conjugated dienes using the N-heterocyclic carbene as a ligand. The unsymmetrical dienes used herein are actually alpha-coupled acrylate - cinnamate combinations bearing two beta-positive carbons and follow the key [2 + 2 + 2] cocyclization pathway.